(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This article explores the significance of interactive techniques in teaching English, emphasizing their role in enhancing student engagement, language acquisition, and effective pedagogical strategies. It reviews current literature, discusses various methods, presents the results of their impact, and concludes with suggestions for the future